2015
DOI: 10.18559/ebr.2015.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Banks, non-bank companies and stock exchange: do we know the relationship?

Abstract: e complex relationship between intrinsic and extrinsic rewards Orni Gov Improvement of the communication between teachers and students in the coaching programme and in a process of action research Review, Vol. 1 (15), No. 4, 2015: 25-45 DOI: 10.18559/ebr.2015Abstract : This paper investigates the role played by the banking sector in founding, sustaining and developing stock exchange markets. The paper has constructed data on market capitalisation separately for banks and non-bank companies. We apply cointegra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The maximum eigenvalue test conducts separate tests on the individual eigenvalues and the null hypothesis is number of cointegrating vectors is equal to 'r' where as the trace test is a joint test where the null hypothesis is that the number of cointegrating vectors is less than or equal to 'r'. Here 'r' is some arbitrary value (Ghimire et al, 2015).…”
Section: Johansen Test Of Cointegrationmentioning
confidence: 99%
“…The maximum eigenvalue test conducts separate tests on the individual eigenvalues and the null hypothesis is number of cointegrating vectors is equal to 'r' where as the trace test is a joint test where the null hypothesis is that the number of cointegrating vectors is less than or equal to 'r'. Here 'r' is some arbitrary value (Ghimire et al, 2015).…”
Section: Johansen Test Of Cointegrationmentioning
confidence: 99%
“…They further argued that the banking sector in developed economies is highly efficient as compared to the developing economies. Moreover, Ghimire et al (2015), concluded that banks have a vital role in the development of stock and capital markets.…”
mentioning
confidence: 99%